Prevalence and Incidence of Human Papillomavirus Infection in Men Having Sex With Men Enrolled in a Pre-exposure Prophylaxis Study: A Sub-study of the Agence Nationale de Recherches sur le SIDA et les Hépatites Virales "Intervention Préventive de l'Exposition aux Risques avec et pour les hommes Gays" Trial. (7th January 2020) - Cotte, Laurent; Veyer, David; Charreau, Isabelle; Péré, Hélène; Cua, Eric; Carette, Diane; Chas, Julie; Capitant, Catherine; Chidiac, Christian; Fléjou, Jean-François; Fouéré, Sébastien; Heard, Isabelle; et al.
Abstract: Background: Human papillomavirus (HPV) infection is more frequent in men having sex with men (MSM) who are living with human immunodeficiency virus (HIV) than in MSM without HIV. There are currently no data regarding HPV infections in preexposure prophylaxis (PrEP)-using MSM. Methods: MSM living without HIV who were enrolled in the Agence Nationale de Recherches sur le SIDA et les Hépatites Virales "Intervention Préventive de l'Exposition aux Risques avec et pour les hommes Gays" PrEP study were prospectively enrolled. Anal, penile, and oral samples were collected at baseline and every 6 months for HPV detection and genotyping. Anal swabs for cytology were obtained at baseline and at 24 months. Results: We enrolled 162 participants. The prevalences of any HPV genotypes at baseline were 92%, 32%, and 12% at the anal, penile, and oral sites, respectively. High-risk (HR) HPV genotypes were observed in 84%, 25%, and 10% of anal, penile, and oral baseline samples, respectively. Nonavalent HPV vaccine genotypes were observed in 77%, 22%, and 6% of anal, penile, and oral baseline samples, respectively. Multiple infections were observed in 76%, 17%, and 3% of cases at the anal, penile, and oral sites, respectively. The most frequent HR genotypes were HPV 53, 51, and 16 in anal samples; HPV 33, 39, and 73 in penile samples; and HPV 66 in oral samples. The incidence of any HPV genotype at the anal site was 86.2/1000 person-months and the incidence of HR-HPV genotypes was 72.3/1000 person-months. The baseline cytology was normal in 32% of cases and was classified as atypical squamous cells of undetermined significance, low-grade squamous intra-epithelial lesion, high-grade squamous intra-epithelial lesion (HSIL), and atypical squamous cells that cannot exclude HSIL in 23%, 40%, 5%, and 1% of cases, respectively. Conclusions: PrEP users have a similar risk of HPV infection as MSM living with HIV and the risk is much higher than that previously reported in MSM living without HIV. Abstract : Prevalences of anal, penile, and oral human papillomavirus (HPV) infections and the incidence of anal HPV infections are high in men having sex with men and using preexposure prophylaxis and comparable in those living without and without human immunodeficiency virus.